2019
DOI: 10.5114/aoms.2018.75864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on insulin resistance and dyslipidemia in overweight and obese premenopausal women

Abstract: Introduction Vitamin D deficiency is a common problem, and it is related to increased risk of obesity, metabolic syndrome, atherosclerosis, and cardiovascular disease. Vitamin D has a beneficial effect on dyslipidemia and insulin secretion. We aimed to investigate the impact of vitamin D 3 supplementation on anthropometric and laboratory parameters in overweight and obese premenopausal women. Material and methods Seventy-two overweight and 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Recent research has confirmed that vitamin D 3 supplementation has a beneficial effect on HOMA-IR and dyslipidemia [59]. Furthermore, in one of the latest studies comparing the HOMA-IR method and insulin resistance (Belfiore) index, it was concluded that insulin resistance (Belfiore) index diagnosed more cases of insulin resistance in women with PCOS compared to HOMA-IR [60]).…”
Section: Discussionmentioning
confidence: 96%
“…Recent research has confirmed that vitamin D 3 supplementation has a beneficial effect on HOMA-IR and dyslipidemia [59]. Furthermore, in one of the latest studies comparing the HOMA-IR method and insulin resistance (Belfiore) index, it was concluded that insulin resistance (Belfiore) index diagnosed more cases of insulin resistance in women with PCOS compared to HOMA-IR [60]).…”
Section: Discussionmentioning
confidence: 96%
“…In a mouse model of T2DM, 8-week supplementation of type 2 diabetes db/db mice with 1,25(OH) 2 D 3 ameliorates hepatic triglyceride accumulation and glucose production via the activation of Ca2+ mediated CaMKKβ/AMPK signaling pathway 68. Imga et al have shown that vitamin D administration in overweight or obese vitamin D-deficient premenopausal women, can result in a significant reduction in LDL-C levels and improvement of IR 69. Effects on vitamin D on postprandial lipid profiles in obese women may be dose-dependent and favors a reduction in LDL and vLDL at lower vitamin D levels, and an elevation of lipids at higher vitamin D doses 70.…”
Section: Vitamin D Regulates Circulating Lipids Blood Pressure and Imentioning
confidence: 99%
“…7 Vitamin D is believed to impact CVD through various mechanisms including impaired glucose and lipid metabolism pathways. 8 Many of these pathways are relevant to insulin resistance as well, given that insulin resistance is a risk factor for dyslipidemia and low levels of serum 25 (OH)D. 9 Although the association between 25(OH)D and serum lipid profile has been reported in numerous studies, 10,11 this association may vary by insulin resistance status. Epidemiological studies suggest an inverse association between 25(OH)D and serum lipid profile 12 although it is highly controversial which lipid may be affected by increased serum 25(OH)D levels.…”
Section: Introductionmentioning
confidence: 99%